ANALISIS KINERJA LULUSAN PROGRAM STUDI MANAJEMEN PENDIDIKAN - Nur Yunisah Ahmad; Sitti Roskina Mas; Arifin Suking (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2022)
This study aims to determine the performance of graduates of the UNG Education Management Study Program in Bone Bolango Regency, in terms of: (1) Integrity (ethics and morals); (2) Expertise based in the field of science (professionalism); (3) Foreign language skills (English); (4) Ability to use information technology: (5) Ability to communicate; (6) Team cooperation ability; (7) Self-development ability. This study applied a quantitative method with a descriptive approach. The number of research subjects was 30 graduate users. Data collection techniques use a questionnaire. The analytical technique used in this research is the descriptive analysis technique using the percentage formula. The results showed that the responses of graduate users on the aspects of: (1) Integrity (ethics and morals) were in a good category; (2) Expertise based on the field of science (professionalism) was in a good category; (3) Foreign language skills (English) was in a very poor category; (4) The ability to use information technology was in a fairly good category; (5) The communication ability was in a good category; (6) The ability of teamwork was in a good category; (7) Self-development ability was in a good category.